Optimizing Critical Thinking Skills of Fourth Grade Students Through Inquiry-Based Learning: Elementary School Mathematics - Syaidi, Azzumardin; Murti, Rahayu Condro (Jurnal Pendidikan MIPA, 2024)
Critical thinking is an important aspect of education that encompasses cognitive, metacognitive, and ethical dimensions. This study aims to examine the impact of inquiry-based learning on students' critical thinking skills in fourth-grade mathematics at elementary school. This research employs a quantitative approach with a quasi-experimental design. This research involves fourth-grade students from Lempuyangwangi Public Elementary School, class A as the experimental group and Class B as the control group. The results of the Paired sample t-test for critical thinking skills in Table 4 between the pretest and posttest of the control class are 8.744 > 1.697 (t table N=30), and for the experimental class, it is 29.078 > 1.699 (t table N=29). In each class, the significance value is 0.001. When compared to the threshold value that must be met for a significance level of 0.05, the calculated significance being less than 0.05 indicates that there is a positive effect. The findings indicate a positive and significant influence of inquiry-based learning on enhancing students' critical thinking skills in mathematics. These results suggest that educators need to consider integrating inquiry-based learning into their teaching strategies to enhance the quality of education.         Keywords: critical thinking, inquiry-based learning, mathematic.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp752-764